Five new species of genus Cryptopimpla Taschenberg (Hymenoptera, Ichneumonidae) with a key to species known in China - Mao-Ling Sheng (ZooKeys, 2011)
Eight species of genus Cryptopimpla Taschenberg, 1863, distributing in China are reported. five of them are new to science: C. flavipedalis Sheng, sp. n., collected from Ningxia Hui Autonomous Region, and C. rufipedalis Sheng, sp. n. collected from Jilin Province, the palearctic part of China. C. carinifacialis Sheng, sp. n., C. flavifacialis Sheng, sp.n. and C. maculifacialis Sheng, sp. n. were collected from Jiangxi Province, the oriental part of China. A key to the species of genus Cryptopimpla Taschenberg known in China is provided.